2006
DOI: 10.1001/archopht.124.6.838
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of Ocular and Visual Retention Following Treatment of Extra-Large Uveal Melanomas by Proton Beam Radiotherapy

Abstract: To assess outcomes of proton beam radiotherapy for the treatment of extra-large uveal melanomas in patients specifically referred to the University of California, San Francisco, for ocular conservation therapy. Series patients uniformly refused enucleation both at an outside institution and again as a treatment option after extensive discussion at the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
51
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 25 publications
5
51
2
1
Order By: Relevance
“…In a previous study, Conway et al [22 ]evaluated ocular retention and visual retention following PBRT in 21 extralarge uveal melanomas. Compared with the present study, choroidal melanomas had a smaller mean tumour thickness (8.6 mm), a larger mean tumour basal diameter (18.7 mm) and ciliary body melanomas were also included.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, Conway et al [22 ]evaluated ocular retention and visual retention following PBRT in 21 extralarge uveal melanomas. Compared with the present study, choroidal melanomas had a smaller mean tumour thickness (8.6 mm), a larger mean tumour basal diameter (18.7 mm) and ciliary body melanomas were also included.…”
Section: Discussionmentioning
confidence: 99%
“…Necrosis after plaque brachytherapy of any kind for malignant intraocular tumors has been reported in 0-33% of patients [1,2,3,4,5]. For uveal melanomas treated with 125 I brachytherapy, necrosis was seen in 11% of patients with predominantly ciliary body involvement [2], while Shields et al [3] reported necrosis in 7% at 5 years and 9% at 10 years in patients with large posterior uveal melanomas.…”
Section: Discussionmentioning
confidence: 99%
“…Scleral necrosis is a known complication of plaque radiotherapy for uveal melanoma, with a reported incidence of 0-33% [1,2,3,4,5]. Proposed mechanisms include a direct necrotizing effect of radiation on the sclera, a secondary effect due to local ischemic inflammation from muscle disinsertion, inflammation related to tumor necrosis, regression of the tumor with undiagnosed scleral invasion, and an occult systemic autoimmune phenomenon [2,4,6].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the neovascular glaucoma rate was 20%, which was not higher than reported in the literature for uveal melanoma in general. As mentioned above, exudative retinal detachment is a risk factor for neovascular glaucoma, which is the leading cause for enucleation [2,4,10,11,12,13]. Therefore, it would be interesting to perform VEGF measurements before and after vitrectomy to show that perhaps by reattachment of the retina, levels of VEGF are lowered to the same levels as in uveal melanoma in general.…”
Section: Discussionmentioning
confidence: 99%
“…Functional outcomes depend inversely on the lag duration between retinal detachment and reattachment. Furthermore, exudative retinal detachment is a risk factor for neovascular glaucoma possibly leading to enucleation with no influence on survival rates [2,4,10,11,12,13]. …”
Section: Introductionmentioning
confidence: 99%